Analysis of user satisfaction graduate in education for Islamic elementary school teachers program UIN Sunan Kalijaga Yogyakarta - Dyaning Wijayanti, inggit; Ekantini, Anita; Wibowo, Fery (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2023)
The aims of this research are 1) to find out the satisfaction of users of Education for Islamic Elementary School Teachers Programme (EIESTP) UIN Sunan Kalijaga Yogyakarta graduates, and 2) to know the analysis of the needs of graduate users to face the transformation of 21st Century Education. The population of this research is users of graduates from EIESTP UIN Sunan Kalijaga Yogyakarta alumni/graduates in 2019, 2020, and 2021. The number of samples is determined by the Slavin formula. Based on the calculation results, the number of samples is 152 graduate users. Data collection instruments are closed questionnaires and documentation. The response results from graduate users are then analyzed using the Customer Satisfaction Index (CSI) method. The research findings show that 1) Satisfaction of users of EIESTP UIN Sunan Kalijaga Yogyakarta graduates with the CSI method was obtained at 94.96% in the very satisfied category, and 2) EIESTP Study Program UIN Sunan Kalijaga Yogyakarta needs to make improvements and increase expertise in the fields of knowledge, collaboration, and integrity ability of its graduates.